Impacts of Hurricane Damage on Southern Highbush Blueberries - Doug Phillips; Jeffrey Williamson; Philip Harmon (EDIS)
Florida has been affected by eight hurricanes since 2000. This new 3-page publication discusses the types of hurricane damage that occur in blueberry production operations, the impacts of these damages, and some recommendations on best management practices in the aftermath of a storm. Written by Douglas A. Phillips, Jeffrey G. Williamson, and Philip F. Harmon and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1342